2006
DOI: 10.1016/j.bbrc.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastasis suppressor 1 (BRMS1) is stabilized by the Hsp90 chaperone

Abstract: Breast cancer metastasis suppressor 1 (BRMS1) is a member of the mSin3-HDAC transcription co-repressor complex. However, the proteins associated with BRMS1 have not been fully identified. Yeast two-hybrid screen, immuno-affinity chromatography, and co-immunoprecipitation experiments were performed to identify BRMS1 interacting proteins (BIPs). In addition to known core mSin3 transcriptional complex components RBBP1 and mSDS3, BRMS1 interacted with other proteins including three chaperones: DNAJB6 (MRJ), Hsp90,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 46 publications
3
66
0
Order By: Relevance
“…These studies however, did not involve microdissected tumor material that would ensure purity of the starting material in a heterogeneous tumor mass. Moreover, it has recently been shown that BRMS1 protein is stabilized by Hsp90 and that its turnover is proteosome-dependent [14]. Thus, assessment of BRMS1 mRNA may not be correlative to the protein levels of BRMS1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies however, did not involve microdissected tumor material that would ensure purity of the starting material in a heterogeneous tumor mass. Moreover, it has recently been shown that BRMS1 protein is stabilized by Hsp90 and that its turnover is proteosome-dependent [14]. Thus, assessment of BRMS1 mRNA may not be correlative to the protein levels of BRMS1.…”
Section: Discussionmentioning
confidence: 99%
“…BRMS1 has also been reported to suppress NFκ-B signaling through blockage of IκBα [11][12][13]. Further, BRMS1 gene regulatory mechanisms have been shown to involve histone deacetylases [14,15]. Proteomic as well as genomic analysis strategies have been used to reveal downstream targets of BRMS1 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these effects may be indirect and attributed to the activity of HDAC6 as a regulator of HSP90 chaperone functions Murphy et al, 2005;Hurst et al, 2006;Kong et al, 2006).…”
Section: Nuclear Targets Of Hdac6mentioning
confidence: 99%
“…Accordingly, HDAC6 appears to play a role, directly or indirectly via HSP90, in the control of the stability of HIF-1a, a transcriptional regulator involved in tumor angiogenesis (Qian et al, 2006), the breast cancer metastasis suppressor 1, BRMS1 (Hurst et al, 2006), Bcr-Abl, FLT-3, c-Raf and AKT (Bali et al, 2005).…”
Section: Hdac6: a Therapeutic Target?mentioning
confidence: 99%
“…Bmi-1, a component of the Polycomb PRC1 complex that suppresses gene expression, is a critical regulator of stem cell self-renewal (Molofsky et al, 2003). Mrj, itself, has been implicated in transcriptional regulation (Dai et al, 2005;Hurst et al, 2006;Pan et al, 2008) and, at least in trophoblast cells, has a ''speckled'' nuclear expression pattern (Watson et al, 2007) reminiscent of Bmi-1 expression in other cell types (Stauffer et al, 2001). As a result, we hypothesized that Bmi-1 may be a substrate for Mrj.…”
Section: Bmi-1 Self-renewal Factor Is Not a Substrate For Mrj During mentioning
confidence: 99%